Concepts of healthcare for women from a quilombola community in the metropolitan area of Fortaleza (CE): an investigation via affections - Morais, Tauanaiara Nogueira de; Rocha, Nara Maria Forte Diogo (Saúde e Sociedade, 2022)
This study aims to investigate health care settings with the participation of women from a quilombola community next to Fortaleza (CE). We highlight the importance of discussing the affective dimension of health practices based on the daily lives of communities, considering socio-political issues such as the ethnic-racial debate. We aimed to identify participants’ health concepts and demands and, discuss ways of thinking and acting in health base on them. The Affective Map Generator Instrument was used to capture issues related to care based on affections. In total, 13 women between the ages of 38 and 77 years participated in this survey. We categorized four care settings based on their answers: evangelical churches, home, community spaces, and shopping centers. Participants gave less important to other spaces, which showed greater variability. We found the relevance collectivity, access, territory, and affections have in building participants’ health processes. Finally, we discuss ways of doing institutionalized care in health services and point out issues for the construction of more dialogical processes which value autonomy.